2010
DOI: 10.3109/02841851003645744
|View full text |Cite
|
Sign up to set email alerts
|

Rice and perfluorocarbon liquid pads: Comparison of fat suppression effects

Abstract: The rice pad exhibited better performance in improving the fat suppression effect. Thus, the rice pad is a superior product that is inexpensive and simple to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Several studies [7][8][9] report that the use of rice pads improved magneticˆeld inhomogeneity, which supports ourˆnding of reduced geometric distortion on EPI DWI, and the pads did this by improv-ing the fat suppression eŠect using CHESS. Thus, ndings of the previous reports and the results of our study represent 2 diŠerent phenomena-improved inhomogeneity of the fat suppression eŠect in CHESS and reduced geometric distortion in DWI using EPI.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Several studies [7][8][9] report that the use of rice pads improved magneticˆeld inhomogeneity, which supports ourˆnding of reduced geometric distortion on EPI DWI, and the pads did this by improv-ing the fat suppression eŠect using CHESS. Thus, ndings of the previous reports and the results of our study represent 2 diŠerent phenomena-improved inhomogeneity of the fat suppression eŠect in CHESS and reduced geometric distortion in DWI using EPI.…”
Section: Discussionsupporting
confidence: 51%
“…[2][3][4] One way to lessen the eŠect of magnetic susceptibility is to place a material with magnetic susceptibility similar to that of the human body at the boundary of the air and human body, [5][6][7][8][9] and the usefulness of rice pads for this purpose has recently been reported. [7][8][9] Because their similar magnetic susceptibility to that of the human body can improve susceptibility eŠect, we hypothesized that rice pads could reduce the geometric distortion in DWI using EPI.…”
Section: Introductionmentioning
confidence: 99%
“…Reported methods to improve CHESS imaging in MR imaging have included the use of pads filled with perfluorocarbon liquid, 13 physiological saline, 14 and rice, [7][8][9][10] but the use of flour has not been reported. When we used flour, lingering fat signals in CHESS decreased in number in the phantom experiment and disappeared in the popliteal space in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations performed with this method in the neck, shoulder, elbow, wrist, and knee have yielded good fat suppression. [7][8][9][10] Rice is widely consumed in such places as Japan, China, India, and other Asian countries, 11 but we questioned whether an alternative material similarly easy to obtain in other countries might be used for such pads to improve CHESS images. We hypothesized that flour from wheat would be a candidate because its raw material, wheat, is consumed around the world, 12 and flour is a processed food product, more easily purchased than unthreshed wheat, and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…41 There are other successful materials in this regard: Moriya et al reported in 2010 that bags of dried rice performed better for improving fat suppression near air interfaces than did the perfluorocarbon liquid. 42 Active strategies Local control of B 0 distortion through strategically placed electrical coil loops To combat field distortion in the inferior frontal lobe resulting from air pockets in the sinuses and nasal cavity, Hsu and Glover reported in 2005 on the use of a set of three small coil loops that could operate intraorally. 43 This part of the brain is a frequent site of B 0 field distortion, which is particularly problematic for fMRI studies.…”
Section: Susceptibility Matchingmentioning
confidence: 99%